Heuristics algorithms for a heterogeneous fleets vrp with excessive demand for the vehicle at the pickup points, and the longest traveling time constraint: A case study in Prasitsuksa Pongkloe, Ubonratchathani Thailand - Sasitorn Kaewman; Raknoi Akararungruangkul (Logistics, 2018)
This paper presents a methodology to solve a special case of the vehicle routing problem (VRP) called the heterogeneous fleets VRP with excessive demand of the vehicle at the pickup points, and the longest time constraint (HFVRP-EXDE-LTC). We developed two metaheuristics-a differential evolution (DE) algorithm and an adaptive large neighborhood search (ALNS)-to solve the problem. These two proposed methods have been designed to effectively solve a special case of VRP. From the computational results, we can see that the proposed heuristics outperformed the best practices that are currently in use. The DE yielded a 9.78% lower cost than that of the current practice (757,250 baht per year), while ALNS generated a 10.89% (906,750 baht per year) lower cost than that of current practice. Comparing the proposed heuristics, ALNS achieved a 1.01% lower cost than that of DE, as ALNS had a better mechanism that was designed to escape from the local optimal.
Keywords: 650; vehicle routing problem; adaptive large neighborhood search; differential evolution algorithm; pickup and delivery system; school bus